Characteristics of and factors associated with infectious disease hospital admissions in children by HIV-exposure status in an era of high coverage of prevention of vertical HIV transmission in the Western Cape Province of South Africa - De Beer, Shani (Department of Public Health and Family Medicine, 2025)
In South Africa, an estimated 22% of children under age 15 years are exposed to HIV and uninfected (HEU). Since the implementation of lifelong antiretroviral therapy (ART) for all pregnant women living with HIV in 2013 (Option B+) and all individuals living with HIV in 2016 (Universal ART), the proportion of children conceived while their mothers are on ART has increased. Previous research suggests that improved maternal health, due to ART, reduces the excess risk of poor health outcomes, including infectious disease hospital admissions, among children HEU vs. children unexposed to HIV and uninfected (HUU). Conversely, ART initiation before conception may result in higher risk of adverse birth outcomes (e.g. preterm delivery, which may drive increased risk of subsequent mortality and morbidity) compared to ART initiation after conception. Using routine healthcare data from the Western Cape (WC) Provincial Health Data Centre, this research aims to characterise the temporal changes in HIV-related characteristics of hospitalised children and their mothers and investigate whether child infectious morbidity and healthcare utilisation vary by HIV exposure and maternal ART use status, during the Option B+ and Universal ART eras. The sample size of children included in this research ranges across chapters from N=52,811 (children with infectious disease admissions 2008 – 2021) to N=549,782 (all children born 2008 – 2018). This thesis uses standardised definitions to systematically classify HIV exposure status of each child. It then describes changes in HIV-related characteristics of children with infectious disease hospitalisations across the WC from 2008 to 2021, showing a decrease in the proportion of admitted children living with HIV and an increase in the proportion of HIV- exposed children exposed to ART from conception, which highlights the success of HIV vertical transmission programmes. A comparison of infection-related hospitalisation rates demonstrates that children HEU vs. HUU experience higher rates of hospitalisation, irrespective of maternal ART history, during the first year of life. Finally, complete routine child healthcare clinic visit attendance among children HEU is seen to be associated with maternal ART start before pregnancy with no gaps in ART care, compared to maternal ART start later in pregnancy with or without gaps in ART. This thesis concludes that better coverage and implementation of existing interventions, as well as the introduction of more multi-faceted interventions, is required to ensure that both children HEU and HUU survive and thrive. Furthermore, this thesis demonstrates that electronic healthcare platforms play an important role in identifying children that require additional support and targeted interventions.